Characteristics of Pyroptosis-Related Subtypes and Novel Scoring Tool for the Prognosis and Chemotherapy Response in Acute Myeloid Leukemia - Pan, Jingjing; Jiang, Yinyan; Li, Changhong; Jin, Ting; Yu, Kang; Jin, Zhenlin (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is usually associated with poor prognosis and low complete remission (CR) rate due to individual biological heterogeneity. Pyroptosis is a special form of inflammatory programmed cell death related to the progression, treatment response and prognosis of multiple tumors. However, the potential connection of pyroptosis-related genes (PRGs) and AML still remains unclear. We described the genetic and transcriptional alterations of PRGs in 151 AML samples and presented a consensus clustering of these patients into two subtypes with distinct immunological and prognostic characteristics. The cluster A, associated with better prognosis, was characterized by relatively lower PRG’s expression, activated immune cells, higher immune scores in tumor microenvironment (TME) and down-regulation of immunotherapy checkpoints. Subsequently, a PRG-score was constructed to predict overall survival (OS) of AML patients by using univariate and multivariate Cox regression analysis, and its immunological characteristics and predictive capability were further validated by 1054 AML samples in external datasets. Besides with immune-activated status, low PRG-score cohorts exhibited higher chemotherapeutic drug sensitivity and significant positive-correlation with the cancer stem cell (CSC) index. Combined with age, clinical French-American-British (FAB) subtypes and PRG-score, we successfully constructed a nomogram to effectively predict the 1/3/5-year survival rate of AML patients and the predictive capability was further validated in multiple external datasets with high AUC value. The various transcriptomic analysis helps us screen significant pyroptosis-related signatures of AML and provide a new clinical application of PRG scores in predicting the prognosis and benefits of treatment for AML patients.